Scope to improve: a multi-centre audit of 16 064 colonoscopies looking at caecal intubation rates, over a 2-year period. Issue 3 (1st May 2012) - Verma, Ajay Mark; McGrath, Nadine; Bennett, Paula; de Caestecker, John; Dixon, Andrew; Eaden, Jayne; Wurm, Peter; Chilton, Andrew
Abstract : Objective: Colonoscopy is the 'gold standard' assessment for large bowel mucosal pathology, but a complete examination is essential. The first national colonoscopy audit carried out in 1999 demonstrated caecal intubation rates (CIRs) of 56.9%. As a result, the Joint Advisory Group (JAG) on gastrointestinal endoscopy launched a programme of continuous quality improvement. JAG recommends that practitioners undertake 100+ procedures per annum with a target CIR of 90%. This current audit provides an assessment of performance against this quality standard. Design: Data were collected from all procedures undertaken in 2008–2009 from six hospitals across three English regions. Results: 16064 colonoscopies performed: CIR = 90.57% (95% CI 90.11% to 91.01%). Operators doing 100+ procedures per annum, CIR=91.76% (91.24% to 92.25%). Operators doing <100 procedures per annum, CIR=87.77% (86.82% to 88.67%). Gastroenterologists, CIR=91.01% (90.32% to 91.70%). Surgeons, CIR=91.03% (90.27% to 91.79%). Other practitioners, CIR=81.51% (78.79% to 84.22%). Bowel cancer screening programme (BCSP) colonoscopies, CIR=97.71% (97.07% to 98.34%). Non-screening colonoscopies, CIR=88.31% (95% CI 87.68% to 88.94%). Conclusion: This audit of 16064 colonoscopies across three regions demonstrates aggregated achievement of the CIR quality standard. However, there is a significant performance gap when comparing BCSP colonoscopists with non-screening colonoscopists and the overall CIR of >90% is supported by the volume of BCSP colonoscopy. Endoscopists performing low volume colonoscopy (<100 per annum), have CIR of <90%. Endoscopists with low volume practice who do not meet the quality standards should engage in skills augmentation plus further training and increase volume of colonoscopy with local mentorship, or stop performing colonoscopy.